Canadian News Coverage of Intimate Partner Homicide: Analyzing Changes Over Time. (July 2013) - Fairbairn, Jordan; Dawson, Myrna
News coverage of intimate partner homicide can reveal and reproduce societal assumptions and beliefs that may influence social and political responses to violence against women. This study analyzes all male-perpetrated intimate partner homicides reported in three daily newspapers in Toronto, Canada within two separate time periods (1975-1979 and 1998-2002) to explore if and how this coverage has changed over time. Results suggest that, in more recent years, news coverage is more likely to report a previous history of intimate partner violence and less likely to employ news that excuses or justifies the perpetrator's actions. However, coverage continues to employ victim-blaming news frames and to portray intimate partner homicide as an individual event, in part, through the absence of the voices of violence against women organizations, researchers, and service providers as legitimate authorities in both time periods. Thus, news coverage fails to encourage social and political responses to violence against women in intimate relationships that emphasize the need for social structural changes focusing on gender equality.